Transcriptomic Study Reveals Recovery of Impaired Astrocytes Contribute to Neuroprotective Effects of Danhong Injection Against Cerebral Ischemia/Reperfusion-Induced Injury - Qian, Jing; Zhao, Xiaoping; Wang, Weiting; Zhang, Shujing; Hong, Zhuping; Chen, Xiaoling; Zhao, Zhuanyou; Hao, Chunhua; Wang, Chenchen; Lu, Shihai; Zhao, Buchang; Wang, Yi (Frontiers in Pharmacology, 2018)
Danhong Injection (DHI) is widely used in clinic for treating cardiovascular and cerebrovascular diseases in China. However, the mode of action of DHI for neuroprotection remains unclear. In the present study, we deemed to investigate the effects of DHI on a rat model of cerebral ischemia/reperfusion injury (IRI) with an emphasis on its regulated gene profile obtained from microarray assays. Firstly, we showed that a 14-day DHI treatment effectively ameliorated severity of neurological deficits, reduced size of ischemic damage, improved status of oxidation stress as well as systemic inflammation for IRI rats, along with which was a pronounced reduced cell infiltration in the area of periaqueductal gray matter. Secondly, bioinformatic analyses for the 429 differentially expressed genes (DEGs) regulated by DHI treatment pointed out ECM-receptor interaction, neuroactive ligand-receptor interaction, and endocytosis as the top 3 biological processes, whilst Toll like recptor 4 (TLR4) as the most relavant singalling molecule. Lastly, we provided evidences showing that DHI might directly protect primary astrocytes from oxygen and glucose deprivation/re-oxygenation (OGD/Re) injury, the effects of which was associated with LAMC2 and ADRB3, two DEGs related to the top 3 biological processes according to transcriptomic analysis. In conlusion, we reported that DHI might work through maintaining the integrity for brain blood barrier (BBB) and to regulate TLR4 related signaling pathway to diminish the inflammation, therefore effectively improved the outcomes of IRI. Our findings suggested that the attenuated astrocytic dysfunction could be a novel mechanism contributing to the neuroprotective effects of DHI against cerebral ischemia/reperfusion-induced damage.